Cultural Violence towards the LGBTQ+ Community in Islamic Majority Country: A Case From @tabu.id’s Comment Section - Siti Ivadhea Harrisa; Nokia Putri Andika Lainsyamputty (Department of Religious Studies, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2022)
Indonesia is a Muslim-majority country. Therefore, Islamic values can be found in every aspect of national and state life. The privilege and power that Muslims have as the majority were used to structurally marginalize the minority group. It changes the essence of religious people who worship God into fanaticism that deifies religion. This study aims to explore the mechanism of cultural conflict and violence against the LGBTQ+ community in the online landscape, primarily through the @tabu.id platform after the pandemic hit. This research uses theories of cultural violence from Johan Galtung and cultural hegemony from Antonio Gramsci. This research uses a thematic analysis method from the comment section of @tabu.id posts. From 19 LGBTQ+ themed posts in @tabu.id from March 2020 to November 2021, it was found that some audiences still perceive LGBTQ+ as a deviation, mainly from Indonesian and Islamic values. This leads to the justification of cultural violence towards the LGBTQ+ community and the rejection of acknowledging LGBTQ+ as part of CSE. These findings show the importance of CSE integrated curriculum that included the LGBTQ+ matter to form an inclusive society. Peace study is also seen as the solution to solve the cultural conflict, violence, and hegemony in Indonesia.